2017
DOI: 10.17796/1053-4628-41.4.280
|View full text |Cite
|
Sign up to set email alerts
|

Deproteinizing Agents as an Effective Enamel Bond Enhancer-An in Vitro Study

Abstract: Among deproteinizing agents, deproteinization when carried out with bromelain gel and sodium hypochlorite showed effective bond strength as compared to papain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 1 publication
4
9
1
Order By: Relevance
“…e mean SBS of the bromelain-treated group after application of 37% acid phosphoric was not significantly different from that of the group only etched with 37% phosphoric acid (G5), which is in agreement with a previous study [11]. e similarity of the results may be due to the use of bromelain after the acid etching process.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…e mean SBS of the bromelain-treated group after application of 37% acid phosphoric was not significantly different from that of the group only etched with 37% phosphoric acid (G5), which is in agreement with a previous study [11]. e similarity of the results may be due to the use of bromelain after the acid etching process.…”
Section: Discussionsupporting
confidence: 90%
“…In line with our results, Hasija et al compared the effect of papain gel on the SBS of composite resin to primary teeth enamel and found no statistically significant difference between the groups [11]. In contrast to the results of the present study, some previous studies indicated that enamel deproteinization with papain gel increased the shear bond strength, irrespective of the acid phosphoric etching application [5,8,10].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In another study, removal of unsupported collagen fiber with bromelain enzyme after acid etching improved the SBS. 4 Hasija et al 24 reported that deproteinization conducted with bromelain exhibited effective bond strength as compared to papain, but it was not statistically significant. However, in our study, there were no significant differences between the specimens exposed to bromelain enzyme before two adhesive systems, which could be attributed to the different step of applying deproteinization agent as we applied it before etching.…”
Section: Resultsmentioning
confidence: 99%
“…e225 In a previous study by Espinosa et al (12), the effect of 5.25% sodium hypochlorite applied for 30 and 60 seconds prior to acid etching on the topographical features of the enamel surface was investigated by scanning electron microscopy (SEM) analysis, and it was reported that the quality of the etching pattern was superiorly enhanced after the 60-second application. Other studies have similarly used the deproteinization duration of 60 seconds (9,11,16,20,21). Therefore, in the present study, both deproteinizing agents were applied for 60 seconds.…”
Section: Discussionmentioning
confidence: 99%